Single-cell transcriptome combined with genetic tracing reveals a roadmap of fibrosis formation during proliferative vitreoretinopathy - Mengyu Liao; Zhisheng Ye; Yumeng Zhao; Jiaying Nan; Yuming Liu; Xueming Yao; Tianjing Yang; Ju Guo; Xin Jin; Hong Zhang; Caiyun You; Heping Xu; et al. (Proceedings of the National Academy of Sciences, 2025)
Ocular fibrosis, a severe consequence of excessive retinal wound healing, can lead to vision loss following retinal injury. Proliferative vitreoretinopathy (PVR), a common form of ocular fibrosis, is a major cause of blindness, characterized by the formation of extensive fibrous proliferative membranes. Understanding the cellular origins of PVR-associated fibroblasts (PAFs) is essential to decipher the mechanisms of ocular wound healing. In this study, we combined single-cell transcriptomics with genetic lineage tracing to map the contributions of retinal pigment epithelial (RPE) cells, immune cells, and Müller cells to disease progression. RPE cells were found to constitute the largest fraction of cells within PVR lesions, transitioning through metabolic, proliferative, and epithelial-to-mesenchymal transition stages during their conversion to PAFs. These cells exhibited remarkable plasticity and heterogeneity. Notably, Pdgfrb + RPE cells demonstrated significant morphological plasticity, transitioning toward a fibroblast-like phenotype, while macrophage-like RPE cells acquired inflammation-related functions post-PVR. Cell communication network analysis identified Thbs1 (encoding TSP-1) as a key hub gene driving RPE cell fate transitions during PVR. Importantly, therapeutic antibodies targeting TSP-1 significantly mitigated PVR progression. This study provides a detailed roadmap of fibrosis formation during ocular wound healing and highlights the therapeutic potential of targeting TSP-1 in the management of PVR.